1997
DOI: 10.1176/ajp.154.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Resemblance of psychotic symptoms and syndromes in affected sibling pairs from the Irish Study of High-Density Schizophrenia Families: evidence for possible etiologic heterogeneity

Abstract: 1997; 154:191-198)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(14 citation statements)
references
References 57 publications
(44 reference statements)
3
11
0
Order By: Relevance
“…Three other studies not reporting an affective dimension chose to focus on nonaffective symptoms in their analyses [17,37,39]. Of the studies reporting affective dimensions, all but 7 found separate manic and depressive dimensions [31,33,38,4143,45]. McGrath et al [31] included limited coverage of affective symptoms, which resulted in a single inclusive affective dimension.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three other studies not reporting an affective dimension chose to focus on nonaffective symptoms in their analyses [17,37,39]. Of the studies reporting affective dimensions, all but 7 found separate manic and depressive dimensions [31,33,38,4143,45]. McGrath et al [31] included limited coverage of affective symptoms, which resulted in a single inclusive affective dimension.…”
Section: Resultsmentioning
confidence: 99%
“…All but one study agreed on a class reminiscent of Kraepelin’s description of dementia praecox , although the nomenclature of this empirically derived class varied among studies: classic schizophrenia [44,63,64]; Kraepelinian schizophrenia [46]; prominent delusions, flat affect, thought disorder [45]; and mixed psychotic [47]. This class was characterized by poor outcome and high levels of positive and negative symptoms, whereas varying levels of disorganization and affective symptoms were observed among studies.…”
Section: Resultsmentioning
confidence: 99%
“…Affective symptoms are common in schizophrenia, and factor analytic studies consistently identify affective dimension among other symptom factors of schizophrenia [65,66]. It has been demonstrated that affective symptoms show high heritability in schizophrenia [67], and some studies indicate genetic factors influencing the risk of affective symptoms among patients with schizophrenia [38,39,68,69,70]. Additionally, in a recent review, authors claim that schizophrenia is primed for an increased expression of affective symptoms, mainly through the activation of immune-inflammatory pathways [71].…”
Section: Discussionmentioning
confidence: 99%
“…For example symptom factors including positive, negative and affective symptoms 11 , thought withdrawal, thought insertion, thought broadcasting and delusions of control 12 and disorganization 13, 14, 15 have been found to be significantly correlated in sibling pairs (including twins) concordant for psychotic illness. Moreover, a meta-analysis of family-based studies of BPD demonstrated statistically significant familial aggregation for the psychosis phenotype 5 .…”
Section: Heritability Of Psychosismentioning
confidence: 99%
“…Negative symptoms are a particularly attractive phenotype for genetic investigation, as they tend to be more stable across the duration of illness, may present prior to the onset of illness, and are often unaffected by antipsychotic drug treatment 43 . Moreover, heritability studies of clinical symptomatology have indicated that affected relative pairs with schizophrenia may share similar severity of negative symptoms more often than expected by chance 11 , indicating a substantial genetic component. Data from several groups suggest that negative symptoms may be influenced by DTNBP1 genotype.…”
Section: Evidence Derived From Candidate Gene Studiesmentioning
confidence: 99%